BIPS . serwis informacyjny Biura Informacji Prasowej KK NSZZ "Solidarność", no. 245, 1981 - Biuro Informacji Prasowej "Solidarność", [ed. Andrzej Zarębski et al.] ([s.n.], 1981)
Print run: 18000 copies